Effect of epidural spinal cord stimulation after chronic spinal cord injury on volitional movement and cardiovascular function: study protocol for the phase II open label controlled E-STAND trial. Issue 7 (18th July 2022) - Darrow, David P; Balser, David Young; Freeman, David; Pelrine, Eliza; Krassioukov, Andrei; Phillips, Aaron; Netoff, Theoden; Parr, Ann; Samadani, Uzma
Abstract : Introduction: Spinal cord injury (SCI) leads to significant changes in morbidity, mortality and quality of life (QOL). Currently, there are no effective therapies to restore function after chronic SCI. Preliminary studies have indicated that epidural spinal cord stimulation (eSCS) is a promising therapy to improve motor control and autonomic function for patients with chronic SCI. The aim of this study is to assess the effects of tonic eSCS after chronic SCI on quantitative outcomes of volitional movement and cardiovascular function. Our secondary objective is to optimise spinal cord stimulation parameters for volitional movement. Methods and analysis: The Epidural Stimulation After Neurologic Damage (ESTAND) trial is a phase II single-site self-controlled trial of epidural stimulation with the goal of restoring volitional movement and autonomic function after motor complete SCI. Participants undergo epidural stimulator implantation and are followed up over 15 months while completing at-home, mobile application-based movement testing. The primary outcome measure integrates quantity of volitional movement and similarity to normal controls using the volitional response index (VRI) and the modified Brain Motor Control Assessment. The mobile application is a custom-designed platform to support participant response and a kinematic task to optimise the settings for each participant. The application optimises stimulation settings by evaluating the parameter space using movement data collected from the tablet application and accelerometers. A subgroup of participants with cardiovascular dysautonomia are included for optimisation of blood pressure stabilisation. Indirect effects of stimulation on cardiovascular function, pain, sexual function, bowel/bladder, QOL and psychiatric measures are analysed to assess generalisability of this targeted intervention. Ethics and dissemination: This study has been approved after full review by the Minneapolis Medical Research Foundation Institutional Review Board and by the Minneapolis VA Health Care System. This project has received Food and Drug Administration investigational device exemption approval. Trial results will be disseminated through peer-reviewed publications, conference presentations and seminars. Trial registration number: NCT03026816 .